A slot allocation strategy for clustered ad hoc networks. (7th December 2006) - Huang, Tsung-Chuan; Yao, Chin-Yi
This work studies the allocation of bandwidth resources in wireless ad hoc networks. The Highest-Density Clustering (HDC) algorithm is presented to promote reuse of spatial channel, and a fair-slot allocation algorithm is proposed to achieve conflict-free scheduling for transmissions. Since the location-dependent contention is an important characteristic of ad hoc networks, in this paper we consider this feature of ad hoc networks to present a new cluster-formation algorithm, by increasing the number of simultaneous links to enhance spatial channel reuse. Furthermore, because each cluster has its own scheduler and schedulers operate independently of each other, the transmissions may conflict among the clusters. In this paper, we classify the flows by the locations of their end points to prevent this problem. Finally, the proposed mechanism is implemented by simulation, and the results reveal that conflicts can be efficiently avoided without global information and network throughput is improved without violating fairness.